Direct terrestrial-marine correlation demonstrates surprisingly late onset of the last interglacial in central Europe - Sier, M.J.; Roebroeks, W.; Bakels, C.C.; Dekkers, M.J.; Brühl, E.; De Loecker, D.; Gaudzinsky-Windheuser, S.; Hesse, N.; Jagich, A.; Kindler, L.; Kuijper, W.J.; Laurat, T.; et al. (Elsevier, 2011)
An interdisciplinary study of a small sedimentary basin at Neumark Nord 2 (NN2), Germany, has yielded a high-resolution record of the palaeomagnetic Blake Event, which we are able to place at the early part of the last interglacial pollen sequence documented from the same section. We use this data to calculate the duration of this stratigraphically important event at 3400 ± 350 yr. More importantly, the Neumark Nord 2 data enables precise terrestrial–marine correlation for the Eemian stage in central Europe. This shows a remarkably large time lag of ca. 5000 yr between the MIS 5e ‘peak’ in the marine record and the start of the last interglacial in this region.
Keywords: Aardwetenschappen; Aardwetenschappen; Blake Event; Eemian; Last interglacial; MIS 5e; Palaeomagnetism